2017
DOI: 10.1111/ejn.13688
|View full text |Cite
|
Sign up to set email alerts
|

Trial‐by‐trial co‐variation of pre‐stimulusEEGalpha power and visuospatial bias reflects a mixture of stochastic and deterministic effects

Abstract: Human perception of perithreshold stimuli critically depends on oscillatory EEG activity prior to stimulus onset. However, it remains unclear exactly which aspects of perception are shaped by this pre-stimulus activity and what role stochastic (trial-bytrial) variability plays in driving these relationships. We employed a novel jackknife approach to link single-trial variability in oscillatory activity to psychometric measures from a task that requires judgement of the relative length of two line segments (the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
67
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(82 citation statements)
references
References 123 publications
(239 reference statements)
12
67
1
Order By: Relevance
“…To test this prediction, we analyzed how prestimulus power is related to the ERD magnitude, and in turn to the amplitude of the late ERP component. We found that trials with strong prestimulus power were related to strong ERD magnitude, consistent with previous studies (Min et al, 2007;Becker et al,2008;Tenke et al, 2015;Benwell et al, 2017a). Due to circularity in these measures (i.e., ERD is computed with prestimulus power), the statistical estimates of this relationship are inflated.…”
Section: Baseline-shift Mechanismsupporting
confidence: 90%
See 1 more Smart Citation
“…To test this prediction, we analyzed how prestimulus power is related to the ERD magnitude, and in turn to the amplitude of the late ERP component. We found that trials with strong prestimulus power were related to strong ERD magnitude, consistent with previous studies (Min et al, 2007;Becker et al,2008;Tenke et al, 2015;Benwell et al, 2017a). Due to circularity in these measures (i.e., ERD is computed with prestimulus power), the statistical estimates of this relationship are inflated.…”
Section: Baseline-shift Mechanismsupporting
confidence: 90%
“…The idea that the ERD contributes to the generation of the slow ERP component, implies that the larger the ERD, the stronger the slow ERP component. Accordingly, we predicted that states of strong prestimulus power would yield a strong ERD (Min et al, 2007;Becker et al, 2008;Tenke et al, 2015;Benwell et al, 2017a), resulting in an enhancement of the slow ERP component during the late time window.…”
Section: Introductionmentioning
confidence: 99%
“…While this may appear to be small, and is an order of magnitude smaller than the typical alpha band width, some studies have identified brain-behaviour relationships with absolute effect sizes well within the range of the non-stationarities we observe here, hence suggesting that changes of this magnitude are of perceptual and cognitive relevance (see Samaha and Postle (2015) and Wutz et al (2018) for reports of perceptually relevant frequency differences of ~0.02-0.04 Hz). In particular, non-stationarities should be considered for the interpretation of M/EEG-behaviour relationships when not only present in the M/EEG signal but also displayed in the employed behavioural measures, as can be the case for psychometric function threshold and slope, detection rate and reaction time (Benwell et al, 2013;Benwell et al, 2018;Doll et al, 2015;Frund et al, 2011). In this situation, a correlation between the two measures of interest may be detected simply because both measures systematically change over time (i.e.…”
Section: Methodological and Applied Considerationsmentioning
confidence: 99%
“…Accordingly, it is plausible that changes in vigilance and fatigue over the course of the experimental session may be related to the shift in alpha power and also frequency observed here. Drifts in oscillatory power within experimental sessions have also been linked to non-stationarities in psychophysical measures (Benwell et al, 2013;Benwell et al, 2018;Bompas et al, 2015;Mathewson et al, 2009) and cognitive processes necessary for the maintenance of task performance (Stoll et al, 2016). In terms of alpha-frequency, previous studies have shown long-term changes over the life-span related to aging and pathology (Aurlien et al, 2004;Klimesch, 1999;Mierau et al, 2017) as well as short-term changes in the sub-second to second range.…”
Section: Understanding Neural Network Activity At the Macro-scalementioning
confidence: 99%
“…91 Participants performed a pitch discrimination task, comparing tone pairs embed-92 ded in noise, as illustrated in Figure 1A. They were instructed to indicate after each 93 tone pair whether the second tone was lower or higher than the first. 94 A black fixation cross was displayed on gray background throughout the whole 95 block.…”
mentioning
confidence: 99%